O parlamentarismo na Constituinte do Rio Grande do Sul de 1947 - Santos, Diego dos (Universidade do Vale do Rio dos Sinos, 2022)
The present study aims to analyze the Constituent of the State of Rio Grande do Sul of 1947, which in the enacted version instituted the parliamentary system of government in the state. For this purpose, a set of historical sources organized using the content analysis method was used in the research. As main sources, the Annals of the Constituent Assembly of Rio Grande do Sul and the newspaper Correio do Povo (RS) were used. The publications of the Diário da Câmara dos Deputados, the Annals of the Federal Senate and the newspapers O Estado de S. Paulo (SP) and O Globo (RJ) were also used. On the other hand, party-political issues developed in the Constituent Assembly process were analyzed from the theoretical perspective of Pierre Bourdieu, based on concepts such as habitus, political field, symbolic power, political discourse and political alliance, as well as the notions of forces ideas (parliamentary and presidentialism) and in the interplay of oppositions and distinctions. between agents and political parties in the field. Thus, from Bourdieu's theory, we tried to understand the establishment of political alliances during the constitutional process of Rio Grande do Sul, with emphasis on the political alliance between PTB and PL and on the game of oppositions between the parties in the political field of the Assembly.
Keywords: Constituinte; Rio Grande do Sul; Parlamentarismo; Aliança política; Campo político; Constituent; Parliamentarism; Political alliance; Political field; ACCNPQ::Ciências Humanas::História